The function of natural compounds in important anticancer mechanisms - Nan, Yang; Su, Hongchan; Zhou, Bo; Liu, Shumin (Frontiers in Oncology, 2023)
The existence of malignant tumors has been a threat to human life and health safety, so finding effective anti-tumor drugs is the world's primary problem to solve. Malignancy is a pathological process in which pathogenic factors are involved in the formation of genetic alterations and various stages of development. Involving genetics, cytology, tissue biology, and pathology, the breadth, and scope of its diversity are daunting. Without timely intervention, metastatic tumor lesions will form and invade surrounding tissues and organs, accompanied by infection, pain, fatigue, and sharp weight loss, leading to multiple organ failures and reducing the survival rate of patients. In recent years, natural compounds are often used as excellent drug preconditions for the prevention and treatment of cancer due to their unique anticancer properties, good efficacy, low toxicity, and no obvious side effects. It targets two cell death pathways, cell apoptosis, and immunogenic cell death, affects the expression of immune cells in the tumor microenvironment, regulates the environment of inflammation and related pathways, and also has certain therapeutic, intervention, and regulatory effects in tumor metastasis. In this paper, natural compounds are classified into phenols, flavonoids, terpenoids, alkaloids, and other classes. The therapeutic effects of natural compounds on cancer are reviewed from the above perspectives, to provide an effective reference for clinical anti-tumor research of natural compounds.